2004
DOI: 10.1124/jpet.104.076190
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Metabolism of Nitric Oxide-Donating Aspirin: The Effect of Positional Isomerism

Abstract: NO-donating aspirin (NO-ASA) is a potentially important chemopreventive agent against cancer. Since positional isomerism affects strongly its potency in inhibiting colon cancer cell growth, we studied the metabolic transformations of its ortho-, meta-, and para-isomers in rat liver and colon cytosolic, microsomal, and mitochondrial fractions as well as in intact HT-29 human colon cancer cells. NO-ASA and metabolites were determined by high-performance liquid chromatography and products identified by mass spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 14 publications
3
36
0
Order By: Relevance
“…Some of them are rapidly metabolized, with little or no formation of aspirin, when incubated in serum, plasma, and rat liver subcellular fractions. 9,12 This behavior is in keeping with the knowledge that the loss of the negative charge by the aspirin molecule, because of the esterification of the COOH group (pK a ) 3.5), makes the acetoxy moiety extremely susceptible to enzymatic cleavage. 21 Interestingly, it was recently found that † A portion of this work was presented as an invited lecture at the 41st International Union of Pure and Applied Chemistry (IUPAC) World Chemistry Congress, August 5-11, 2007 neither aspirin nor NO contributes to the antitumor effect of 2, 4, which, in contrast, is due to the quinone methides formed after carboxylic ester hydrolysis.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…Some of them are rapidly metabolized, with little or no formation of aspirin, when incubated in serum, plasma, and rat liver subcellular fractions. 9,12 This behavior is in keeping with the knowledge that the loss of the negative charge by the aspirin molecule, because of the esterification of the COOH group (pK a ) 3.5), makes the acetoxy moiety extremely susceptible to enzymatic cleavage. 21 Interestingly, it was recently found that † A portion of this work was presented as an invited lecture at the 41st International Union of Pure and Applied Chemistry (IUPAC) World Chemistry Congress, August 5-11, 2007 neither aspirin nor NO contributes to the antitumor effect of 2, 4, which, in contrast, is due to the quinone methides formed after carboxylic ester hydrolysis.…”
Section: Introductionsupporting
confidence: 76%
“…Unlike the previous NO-donor aspirins that seem to require enzymatic metabolism for NO release, [10][11][12] these products proved to release NO under the action of thiols. 13 Intracellular release induced by glutathione is potentiated by ascorbic acid.…”
Section: Introductionmentioning
confidence: 76%
“…In vitro studies have shown that NO-aspirin inhibits COX-1 and COX-2, and that the presence of the spacer and NO-donating moiety in the molecule slows the kinetics of COX-1 inhibition by NCX 4016 compared with aspirin (34). The positional isomer of NO-aspirin used in this study (meta) is converted essentially into salicylic acid, 3-hydroxybenzylalcohol, and a conjugated product between glutathione and the aromatic spacer linking the aspirin moiety to the NOreleasing group (35,36). In rats, following a single administration of NO-aspirin, the main metabolites in plasma were NO x , salicylic acid, and nitrosothiols, with no intact drug observed.…”
Section: Discussionmentioning
confidence: 92%
“…NO-ASA, both para [2-(acetyloxy) benzoic acid 4-(nitrooxy methl) phenyl ester] and meta [2-(acetyloxy) benzoic acid 3-(nitrooxy methl) phenyl ester], was synthesized as previously described (22). Antibodies against the phosphorylated forms of cJun, ATF-2, JNK, p38, ERK1/2, Akt and total p21 were purchased from Cell Signaling Technology, Beverly, MA.…”
Section: Methodsmentioning
confidence: 99%
“…1B, the time-response curves of both isomers follow a similar course: after an initial strong decline during the first 4 h, there is a shallow decrease in the number of viable cells. Although the reason for this biphasic response is unclear, it is conceivable that it reflects the rate of metabolic transformation of NO-ASA (22).…”
Section: Both Isomers Of No-asa Inhibit the Growth Of Colon Cancer Cementioning
confidence: 99%